Medical students' experiences of mistreatment in educational hospitals - sedigheh Ebrahimi; Vahid Reza Zarei (Shiraz University of Medical Sciences, 2018)
Introduction: Mistreatment with medical students is a global phenomenon, which has been proved in several studies. The aim of this study is to investigate the extent of mistreatment that the medical students experience in educational hospitals of Shiraz University of Medical Sciences. Methods: This cross-sectional study was carried out using descriptive-analytical method. All medical students were studied in educational hospitals of Shiraz University of Medical Sciences by census method. A questionnaire with 26 questions was used to collect data on demographic information, experience of mistreatment and observation of mistreatment towards the other students and open-ended questions. Data were analyzed using SPSS version 18 software. Results: The results of the study showed that 86.3% of the students experienced at least one kind of mistreatment during the previous year; among these misbehaved students 57.5% were female and 42.5% were male. The most cases of mistreatment were verbal mistreatment (95.1%) and abuse of authority (76.2%). The highest number of mistreatment has taken place in obstetrics and gynecology(OB-GYN) departments (60.3%) and in internal departments (49.2%), respectively; most of the individuals who misbehaved toward the students were residents (73%),nurses (66.7%), and interns (60.3). Conclusion: Regarding the high prevalence of mistreatment against medical students, there is a need for a plan for training communication skills and more support for students in this field.